Guided Inquiry Learning Model, Simple Practicum Tool, Creative Thinking Skills - Muhammad Zaky (Berkala Ilmiah Pendidikan Fisika, 2019)
The main objective of this research is to produce junior high school Physics teaching materials oriented to a simple practical tool that can be used to foster junior high school students 'creative thinking skills, with the specific aim of knowing the indicators of junior high school students' creative thinking skills that can be grown through the use of a guided inquiry learning model assisted by a simple practicum tool. This type of research is a quasi-experimental research with the design of Equivalent Pretest-Posttest Design (Design of Prates-Pascates Equivalent). This research was conducted at the Labschool Junior High School of Tadulako University where  the class VIII students being the research subjects. The research instrument used was an essay test and observation sheet. The data analysis technique used was quantitative data analyzed by inferential statistics, calculating the significance of the differences in the average of both groups of samples and qualitative data analyzed by using the stages of data reduction, data presentation and conclusion. The results showed that a guided inquiry learning model assisted by a simple practicum tool could foster the creative thinking skills of the students of Labschool UNTAD Junior High School in the indicators of flexible thinking, fluent thinking and originality.